Front Cover: Hydrogen‐Atom Tunneling in Metaphosphorous Acid (Chem. Eur. J. 37/2020). Issue 37 (12th June 2020) - Qian, Weiyu; Chu, Xianxu; Song, Chao; Wu, Zhuang; Jiao, Mengqi; Liu, Hanwen; Zou, Bin; Rauhut, Guntram; Tew, David P.; Wang, Lina; Zeng, Xiaoqing
Abstract : Metaphosphorous acid (HOPO), a heavy analogue of nitrous acid (HONO), has been generated in syn‐ and anti‐ conformations in the gas phase. Surprisingly, anti‐ HOPO is highly unstable and it undergoes rapid rotamerization to syn ‐HOPO via hydrogen‐atom tunneling (HAT) with a lifetime of 10 min in N2 ‐matrix at 2.8 K. More information can be found in the Communication by X. Zeng et al. on page 8205 .